PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN MELALUI PENGELOLAAN BARANG MILIK DAERAH - Wahyuni, Sri; Fadah, Isti; Tobing, Diana Sulianti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Abstract: The purpose of this study is to analyze the influence of human resource competency and utilization of information technology on the financial statement quality mediated by the local property management in the Government of Bondowoso Regency. This is a quantitative research with the population consists of all property administrators, operators of Local Management Information System (SIMDA)/financial report makers, and Financial Administration Officials (PPK). Sampling method used is saturated sampling (census). Data used were collected from questionnaires distribution and analyzed using Structural Equation Modeling (SEM). Results of the research prove that human resource competency affects local property management and financial statement quality, while utilization of information technology only affects financial statement quality, but it has no effect on local property management. In addition, local property management affects financial statement quality. These mean that local property management partially mediates the influence of human resource competency on financial statement quality, but it does not mediate the influence of utilization of information technology on financial statement quality. Keywords: Human Resource Competency, Utilization of Information Technology, Management of Local Property, and Quality of Financial Statement.